The Diagnostic Role of Adiponectin in Pulmonary Embolism - Gul, Evrim; Gul, Yeliz; Yildirim, Ersin; Pepele, Mustafa Safa; Yildiz, Mustafa; Bozdemir, Mehmet Nuri; Ilhan, Necip (Hindawi Ltd, 2016)
Background and Aims. Pulmonary thromboembolism (PTE) is a frequent disease with difficult diagnosis and high mortality. Misdiagnosis occurs in 2/3 patients and mortality rates reach up to 30%. The aim of our study was to investigate the role of adiponectin used in emergency service in diagnosis of PTE. Materials and Methods. 95 patients with suspected PTE included in the study. Plasma adiponectin and D-dimer levels were measured and chest X-ray and multidetector row computed tomography scan obtained. Diagnosis was supported by vascular filling defect on tomography. Control group consisted of patients with suspected PTE and normal chest computed tomography findings. Results. Mean D-dimer level was 4241.66 +/- 1082.98 ng/mL in patients and 2211.21 +/- 1765.53ng/mL in the control group (p <= 0.05). Mean adiponectin level was 5.46 +/- 4.39 mu g/mL in patients and 7.68 +/- 4.67 mu g/mL in the control group (p <= 0.05). Wells and Geneva scores were higher in patients compared to the control group. Conclusions. As a result, we conclude that lower adiponectin levels have an important role in the diagnosis of PTE.
Keywords: Plasma-Protein; Insulin-Resistance; Mortality; Adipose; Link; Fat